PREPARATION AND CHARACTERIZATION OF PERFLUOROETHYLSUBSTITUTED ALKYLAMMONIUM OLIGOFLUOROPHOSPHATES - Mokrushin, Ivan G.; Pinegina, Olga A.; Kransnovskikh, Marina P.; Dmitriev, Maksim V.; Markin, Igor V.; Kozen, Arkadij L. (ChemChemTech, 2024)
Mono-, di-, triperfluoroethyl substituted fluorophosphate anions are building blocks in the molecular design of salts with onium cations, and are used to increase hydrophobicity, modify surfactant properties and electrical conductivity. The work proposes methods for the synthesis of superacid H+[PF3(C2F5)3]- by the reaction of tri(pentafluoroethyl)difluorophosphorane with a solution of hydrofluoric acid, as well as superacids H+[PF4(C2F5)2]- and H+[PF5C2F5]- by step-by-step removal of the pentafluoroethyl substituent by hydrolysis with subsequent treatment with HF solution. Ionic compounds were synthesized by metathesis of anions at 0 °C from the corresponding quaternary ammonium chloride based on the obtained superacids. The article presents NR4FAP-class ionic compounds with the tributylmethylammonium (TBMA) cation of the general formula [(C4H9)3NCH3]+[PF6-n(C2F5)n]-, where n = 1, 2, 3. The square bipyramidal structure of the three studied anions was confirmed by nuclear magnetic resonance (NMR) spectroscopy and X-ray diffraction (XRD) data. The study shows, the synthesized compounds are characterized by extremely low vapor pressure up to 300 °C, a wide range of the liquid state with a width of up to 310 K by the methods of differential scanning calorimetry (DSC) and synchronous thermal analysis (STA). Melting temperatures and enthalpies were determined. The TBMA salts belong to ionic liquids (IL's), including one type liquid at room temperature (RT-IL). The general patterns of compounds decomposition were analyzed by the analysis of evolved gases (STA-EGA); it was shown that in all cases, the decomposition of the studied ionic liquids begins with the destruction of the anion. The electrical resistance of a pure ionic liquid at room temperature was studied. The described characteristics of perfluoroethylsubstituted alkyl ammonium oligofluorophosphates open up prospects for their use as electro conducting and antistatic additives for petrochemicals, fuels and polymers. For citation: Mokrushin I.G., Pinegina O.A., Krasnovskikh M.P., Dmitriev M.V., Markin I.V., Kozen A.L. Preparation and characterization of perfluoroethylsubstituted alkylammonium oligofluorophosphates. ChemChemTech [Izv. Vyssh. Uchebn. Zaved. Khim. Khim. Tekhnol.]. 2024. V. 67. N 5. P. 54-61. DOI: 10.6060/ivkkt.20246705.6916.